(untitled) (Revista Apotheke, 2022)
Under a narrative methodology of professional experiences, a first approximation is presented on the experiences lived and the attitudes observed in a textile art workshop for adolescents in a private secondary school, this workshop is considered as a space for the recovery of the proposal made by the New Educational Model proposed in Mexico by the Ministry of Public Education (SEP) in 2017 around the so-called Areas of Curricular Autonomy that as of 2019 came into disuse. The active observation of the phenomena that occurred in this new workshop encourages reflection on the relationship between the development of manual skills, cognitive processes and the development of socio-emotional skills that arise while adolescents face aesthetic experiences in spaces of trust and cooperation by medium of textile materials and tools.